2020
DOI: 10.4257/oeco.2020.2404.05
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Deficits and High Temperature Increase Leaf Litterfall in Open Restinga Vegetation, in Southern Brazil

Abstract: Climate is an important driver of litterfall along different ecosystems. However, little is known about how climate affects litter production in plant communities of Restinga. The aim of this study is to characterize the temporal variation in leaf litter production in an Open Clusia Formation in Restinga de Jurubatiba National Park, from 2001 to 2018, and assess how local variability in litter production reflects the local climatic conditions and its variability. We tested the hypothesis that monthly leaf litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
2
0
2
Order By: Relevance
“…While precipitation appears to be the strongest driver of phenology, effects of temperature on phenological events have been observed in other tropical forests. The interaction between temperature and leaf dynamics has been observed in southeast Asia and in south America (Marques et al 2004; da Rocha Gripp et al 2020; Kitayama et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…While precipitation appears to be the strongest driver of phenology, effects of temperature on phenological events have been observed in other tropical forests. The interaction between temperature and leaf dynamics has been observed in southeast Asia and in south America (Marques et al 2004; da Rocha Gripp et al 2020; Kitayama et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…é baixo em florestas tropicais (Bruijnzeel 1991), assim como em formações costeiras sazonalmente secas (Jaramillo et al 2011), como as restingas. Nesses ambientes, estima-se que até 90 % de toda a produção primária não seja consumida por herbívoros e, portanto, um grande excedente de matéria orgânica converge para o solo em forma de detritos vegetais (Cebrian 1999), sendo que o folhiço constitui a maior fração dessa matéria orgânica, tanto nas restingas (Gripp et al 2020(Gripp et al , 2023a quanto em âmbito global .…”
Section: Introductionunclassified
“…Nas restingas, a baixa capacidade de retenção de água do solo arenoso pode submeter a comunidade de decompositores a curtos períodos de disponibilidade de água. Dessa forma, apesar de a precipitação não ser baixa (1 100-1 250 mm por ano; Gripp et al 2020) e a estação seca ser pouco marcada, a comunidade de decompositores pode estar submetida a períodos de escassez de água ao longo de todo o ano, o que resultaria em uma baixa taxa de decomposição.…”
Section: Introductionunclassified
“…Besides competitive interactions with C. hilariana, a lower and intermittent water availability at the soil surface to shallow root seedlings may restrict their growth on OCS. It has been previously demonstrated that litterfall rates are correlated to air temperature and precipitation in OCS and, to a lesser extent, in SDF (Brito et al, 2018;Gripp et al, 2020). When temperature increases and rainfall becomes lower than evapotranspiration, soil moisture is depleted, increasing tensions in the xylem sap that can trigger stomatal closure and other physiological responses (Nepstad et al, 2002), limiting tree growth and promoting litterfall peaks (Lawrence, 2005).…”
mentioning
confidence: 99%